Not all immune-checkpoint inhibitors are created equal: Meta-analysis and systematic review of immune-related adverse events in cancer trials. (November 2017) - El Osta, B.; Hu, F.; Sadek, R.; Chintalapally, R.; Tang, S.-C.
Abstract: Background: Targeting immune checkpoints is a novel approach in cancer therapy. This strategy may trigger immune related adverse events (irAE). We hypothesize that the incidence of irAE will be greater in patients receiving immune checkpoint inhibitors (ICI) targeting only immune cells compared to those that also target tumor cells (PD-L1). In addition, we compared the specific irAE profile and overall response rate (ORR) for each ICI by target(s). Materials and methods: We reviewed all ICI cancer clinical trials (90; 174 arms) that reported irAE and were published through MEDLINE. 114 arms from 73 trials were eligible for this meta-analysis (including 11, 328 patients). We collected and compared arm-specific data including ICI target, number of patients with irAE of any grade, grade 3+ and grade 5, specific irAE, and ORR. The R package "meta" was used to conduct a meta-analysis to calculate and compare the percentage of patients with irAE and ORR. Results: The incidence (% of patients) of any grade irAE per ICI target was reported for 40 arms (3418 patients) treated with ICI. Most arms (80%) and patients (53%) studied were on phase 1/2 clinical trials. Patients were treated for solid malignancy on 39 arms (97%), mainly melanoma (40%). Two arms included ICI combinations. The incidence of any grade irAE was higher in patients who received ICI targeting CTLA-4 (53.8%) than PD-1 (26.5%) and PD-L1 ICI (17.1%) ( P  < 0.001). Comparative specific irAE rates were calculated for each ICI target. Conclusions: Our systematic review supported our mechanistic-driven hypothesis. We encourage investigators to report the incidence of irAE in future ICI combination trials.